(untitled) (Applied Biological Research, 2016)
A total of 19 weeds viz., Abutulon theopharasti, Achyranthus aspara, Ageratum conizoides, Cyperus esculentus, Malvestrum coromandelianum, Amaranthus viridis, Boerhavia diffusa, Calotropisgigantean, Cannabis sativa, Commelina benghalensis, Digera arvensis, Eclipta alba, Euphorbia hirta, Tinospora cordifolia, Ipomoea pestigridis, Parthenium hysterophorus, Phylanthus niruri, Physalis minima and Tribulus errestris, belonging to 12 families, were collected from chilli (Capsicum annum) fields in Punjab (India) with the aim to find out alternate hosts of Begomoviruses affecting drastically chilli crop. Of these, Eclipta alba, Ageratum conizoides, Amaranthus viridis, Ipomoea pestigridis, Abutulon theopharasti, Cannabis sativa and Commelina benghalensis showed typical leaf curl symptoms with vein clearing as predominant symptom exhibited by the above symptomatic weed species. Rest weeds did not possess any symptom. All the weed species were subjected to PCR and only Commelina benghalensis was found positive for Begomovirus with expected fragment size of 575 bp of core protein region. Further, rolling circle amplification (RCA) technique was adopted to develop concatemer of circular DNA of virus. The RCA product when used as template in PCR showed amplification ( 575 bp) for all the symptomatic and asymptomatic weed species, except Calotropis gigantean. The phylogenitic analysis revealed the presence of chilli leaf curl India virus, tomato leaf curl Jodepur virus and papaya leaf crumple virus in weed samples. Perusal of literature revealed that Commelina benghalensis aspara, Boerhavia diffuda, Cyperus esculentus, Tinospora cordifolia and Ipomoea pestigridis have not so far been reported as hosts of Begomoviruses, so this is the first report in this direction.